PELATIHAN PENULISAN CERITA ANAK BAGI GURU DAN KEPALA SEKOLAH DASAR DI KOTA JAYAPURA - Yektiningtyas, Wigati; Embram , Esther R.; Sukma, Ratna M.; Enriko, Dennys E.; Modouw, James (LPPM Uncen, 2024)
Papuan children generally like hearing and reading stories with Papuan backgrounds. Unfortunately, there are not many children stories of this kind. Therefore, we feel it is necessary to train elementary school principals and teachers in Jayapura Municipality to write children stories. The aim of this activity is to train principals and teachers (a) to write children stories with Papuan background, (b) understand the stages of writing children stories, (c) to be able to infuse nature and culture and (d) to rewrite folkltales in children language. This activity was carried out in Horison Hotel Padang Bulan in February 2024 and involved teams from Cenderawasih University and the Papua Province Language Center. There were twenty teachers and principals from various elementary schools in Jayapura Municipality attended this training. The team worked together to prepare material about the importance of children stories, the structure of children stories, story grading and story boards. The team also involved Tobati and Skouw language translators because several children stories were translated into those languages. The end of this activity shows that the teachers (1) are able to create children stories with a Papuan background using the rules they have learned; (2) are able to produce children stories based on the reading grades. Besides, translation of the stories into Tobati and Skouw languages can be executed as well.Through this training the principals and teachers are able to produce contextual children story books. Keywords: contextual Papuan children stories; children book leveling; language preservation; Tobati language; Skouw language